2020
DOI: 10.1108/ijis-03-2020-0022
|View full text |Cite
|
Sign up to set email alerts
|

The local innovation agents program: a literature review on the largest Brazilian small business innovation support program

Abstract: Purpose This paper aims to analyze the characteristics of Brazilian micro and small businesses (MSBs) and the main lessons derived from the largest small business innovation support program in the country, the Local Innovation Agents – Agentes Locais de Inovação (ALI) Program. Design/methodology/approach In total, 34 papers were selected from the Web of Science and Scopus databases (28), as well as from the Revista de Administração e Inovação – RAI (6), a seminal Brazilian innovation journal. The papers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 28 publications
(44 reference statements)
0
9
0
10
Order By: Relevance
“…In this way, this study is based on the inquiry carried out by Silva and Di Serio (2017), which indicates weaknesses in the conceptualization of organizational innovation criteria, resulting in a heterogeneous and dispersed conceptual basis (Forsman, 2011;Berends et al, 2014). Silva and Di Serio (2017), present the main weaknesses of innovation theory as follows: i) a lack of conceptual convergence, leading to an inaccurate understanding within and between theoretical fields regarding what innovation truly is (Sawhney et al, 2006); ii) the existence of a high number of innovation typologies, which do not clearly present the unit of analysis, making comparisons between research results unfeasible (Gao et al, 2020;Medeiros, 2021;Carneiro et al, 2021); iii) the lack of a common understanding about the innovation process (Berends et al, 2014;Ferreira et al, 2015); and iv) the popularization of the fallacy that innovation is only technological, which is moreover dependent on R&D activities and is an exclusive privilege of large corporations (Berends et al, 2014;Silva et al, 2016;Silva & Di Serio, 2017), disregarding the innovative role of small companies (McGuirk et al, 2015;De Carvalho et al, 2020).…”
Section: Innovation In Micro and Small Companies: A Conceptual Unders...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, this study is based on the inquiry carried out by Silva and Di Serio (2017), which indicates weaknesses in the conceptualization of organizational innovation criteria, resulting in a heterogeneous and dispersed conceptual basis (Forsman, 2011;Berends et al, 2014). Silva and Di Serio (2017), present the main weaknesses of innovation theory as follows: i) a lack of conceptual convergence, leading to an inaccurate understanding within and between theoretical fields regarding what innovation truly is (Sawhney et al, 2006); ii) the existence of a high number of innovation typologies, which do not clearly present the unit of analysis, making comparisons between research results unfeasible (Gao et al, 2020;Medeiros, 2021;Carneiro et al, 2021); iii) the lack of a common understanding about the innovation process (Berends et al, 2014;Ferreira et al, 2015); and iv) the popularization of the fallacy that innovation is only technological, which is moreover dependent on R&D activities and is an exclusive privilege of large corporations (Berends et al, 2014;Silva et al, 2016;Silva & Di Serio, 2017), disregarding the innovative role of small companies (McGuirk et al, 2015;De Carvalho et al, 2020).…”
Section: Innovation In Micro and Small Companies: A Conceptual Unders...mentioning
confidence: 99%
“…Notably, the application of the innovation radar model in studies on the development of innovation in MSEs in the national context has also indicated a fifth dimension (Néto & Teixeira, 2014;Paredes et al, 2015;De Carvalho et al, 2015;Simões et al, 2015;Gonçalves et al, 2017;De Carvalho et al, 2020), originally called "innovative ambience" (Bachmann & Destefani, 2008), which, in this study, based on the international literature, is renamed "innovation in knowledge channels" (van de Vrande et al, 2009;Parida et al, 2012;Silva et al, 2016). The redefinition of this new approach to innovation is theoretically supported since the literature considers "innovation in knowledge channels" as a form of open innovation (van de Vrande et al, 2009;Parida et al, 2012;Silva et al, 2016).…”
Section: Structure Of An Innovation Assessment Model In Micro and Sma...mentioning
confidence: 99%
See 1 more Smart Citation
“…Organizations cannot stand alone without support from internal and external parties (Dambiski Gomes de Carvalho et al, 2020;Vinyard, 2015). The previous instrument explained that the plans that were prepared had to be submitted to the implementers in the field.…”
Section: Focus On the Market And Customersmentioning
confidence: 99%
“…Alguns trabalhos que estudaram o programa (CAMPELO, 2017;CARVALHO, et al, 2018;GONÇALVES et al, 2017;LIMA;MULLER, 2017;VASCONCELOS;OLIVEIRA, 2018;WALTER et al, 2017;DORNELAS;DALCOMUNI, 2013;OLIVEIRA, 2012;ROCHA, 2015;ALCOFORADO, 2019;CARVALHO et al, 2020;SENHORAS, 2021)…”
unclassified